2022
DOI: 10.1161/circep.122.010955
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radioablation for Ventricular Tachycardia in the Setting of Electrical Storm

Abstract: Background: Stereotactic body radiotherapy (SBRT) has been reported as a safe and efficient therapy for treating refractory ventricular tachycardia (VT) despite optimal medical treatment and catheter ablation. However, data on the use of SBRT in patients with electrical storm (ES) is lacking. The aim of this study was to assess the clinical outcomes associated with SBRT in the context of ES. Methods: This retrospective study included patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Stereotactic radioablation (SBRT) therapy has been emerging as a therapy for refractory VAs despite optimal medical therapy and CA. Ninni et al demonstrated that SBRT significantly reduces the VT burden during ES (mean VT burden reduction: −91% [95% CI, 78–103]; p < 0.0001), but with a transient recurrence in the first 6 weeks, probably linked to the inflammatory response with the necessity of VT tolerance and ICD reprogramming [ 110 ].…”
Section: Bailout Therapiesmentioning
confidence: 99%
“…Stereotactic radioablation (SBRT) therapy has been emerging as a therapy for refractory VAs despite optimal medical therapy and CA. Ninni et al demonstrated that SBRT significantly reduces the VT burden during ES (mean VT burden reduction: −91% [95% CI, 78–103]; p < 0.0001), but with a transient recurrence in the first 6 weeks, probably linked to the inflammatory response with the necessity of VT tolerance and ICD reprogramming [ 110 ].…”
Section: Bailout Therapiesmentioning
confidence: 99%
“…Solving the Reach Problem: A Review of Present and Future Approaches for Addressing Ventricular Arrhythmias Arising from Deep Substrate Lower VA burden and ICD therapy 63 Improved quality of life in multiple small studies [63][64][65] Non-invasive mapping and Lower procedure time Modification of operator strategy in 43% of cases 45 High correlation of between image identified substrate and critical isthmus/LAVA 46 Imaging processing performed at external site Lead time may be required Advances in ablation catheter technologies include the use of higher impedance irrigation, changes in the energy source used for ablation, and pre-ablation cardiac imaging which has been introduced to improve the efficacy of catheter ablation for VT. 9,10…”
Section: New Technologies For Ablation Of Vasmentioning
confidence: 99%
“…The described steps were integrated into a single software, named CardioMerge, that makes use of the state-of -the-art C++ libraries insight toolkit (ITK) 3 and VTK. 3 https://itk.org/…”
Section: Visualization and Target Delineationmentioning
confidence: 99%
“…Cardiac radioablation (CR) recently appeared as a promising technique for treatment of refractory ventricular tachycardia (VT). [1][2][3] Also known as Stereotactic arrhythmia radiotherapy (STAR), 4 or cardiac stereotactic body radiotherapy (cardiac SBRT), 2 this treatment consists in delivering a high radiation dose (20 to 25Gy), in a single treatment session, to the myocardium tissues identified as the source of the VT. Patients suffering from VT undergo a series of treatments, including medications, implantation of an implantable cardioverter-defibrillator (ICD), and invasive catheter radiofrequency ablation (CRF), that constitutes the standard medical care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation